A 3D printed microfluidic perfusion device for multicellular spheroid cultures. (11th September 2017) - Ong, Louis Jun Ye; Islam, Anik; DasGupta, Ramanuj; Iyer, Narayanan Gopalakkrishna; Leo, Hwa Liang; Toh, Yi-Chin
Abstract: The advent of 3D printing technologies promises to make microfluidic organ-on-chip technologies more accessible for the biological research community. To date, hydrogel-encapsulated cells have been successfully incorporated into 3D printed microfluidic devices. However, there is currently no 3D printed microfluidic device that can support multicellular spheroid culture, which facilitates extensive cell–cell contacts important for recapitulating many multicellular functional biological structures. Here, we report a first instance of fabricating a 3D printed microfluidic cell culture device capable of directly immobilizing and maintaining the viability and functionality of 3D multicellular spheroids. We evaluated the feasibility of two common 3D printing technologies i.e. stereolithography (SLA) and PolyJet printing, and found that SLA could prototype a device comprising of cell immobilizing micro-structures that were housed within a microfluidic network with higher fidelity. We have also implemented a pump-free perfusion system, relying on gravity-driven flow to perform medium perfusion in order to reduce the complexity and footprint of the device setup, thereby improving its adaptability into a standard biological laboratory. Finally, we demonstrated the biological performance of the 3D printed device by performing pump-free perfusion cultures of patient-derived parental and metastatic oral squamous cell carcinoma tumor and liver cell (HepG2) spheroids with good cell viability and functionality. This paper presents a proof-of-concept in simplifying and integrating the prototyping and operation of a microfluidic spheroid culture device, which will facilitate its applications in various drug efficacy, metabolism and toxicity studies.